How to support parenting in patients with cancer and co-parents? From research to practice. Issue 4 (9th July 2022) - Liénard, Aurore; Lamal, Salomé; Merckaert, Isabelle
Abstract : Purpose of review: When a parent is diagnosed with cancer, the entire family is impacted. Patients with cancer and co-parents may no longer feel able to fulfill their parenting roles. The aims of this article are to describe interventions designed to support parenting in the oncological context and to make suggestions for the development and assessment of such interventions. Recent findings: Ten parenting support interventions published in the last 10 years in oncology were identified, among which four randomized controlled trials (RCTs). The therapeutic aims, techniques, and modalities of these interventions were heterogeneous. Five main therapeutic aims were addressed to: increase parents' knowledge, promote parents' emotion regulation, enhance parents' self-efficacy related to parenting, promote parents' support of their children's reactions and coping strategies, and promote open and appropriate parent–child communication. Few studies have combined informational resources with experiential techniques. Summary: Very few studies examining the efficacy of parenting support interventions have been published. There is still a need to develop, test, and compare interventions that meet the many needs of parents and their children. Suggestions are made about the contents and formats of parenting support interventions in oncology.